Penelope Heynes at 90 m of Her 100 m Breaststroke Victory at the 1998 Goodwill Games in New York - Rushall, B. S. (1999)
Video pictures (21 frames) and the appropriate technical/ biomechanical explanations for Penelope Heynes at 90 m of Her 100 m Breaststroke Victory at the 1998 Goodwill Games in New York.